Pengembangan Metode Ekstraksi dan Analisis Irbesartan dalam Plasma Darah menggunakan High Performance Liquid Chromatography (HPLC) Fluorescence - Ratih, - (Jurnal Farmasi Indonesia, 2015)
A simple extraction and analysis method by High Performance Liq- uid Chromatography (HPLC) ô°luorescence has developed for determination of Irbesartan in plasma sample. The chromatography system were ô°luorescence detector at Î» ex254nm/em380 nm, ô°low rate 1 mL/min, C-18 150 x 4,6 mm; 5Î¼m column and acetonitrile : 0,5% (v/v) H3PO4 pH 3,0 (77:23) as mobile phase by run time not more than 6 minutes. Reliability of the HPLC method was as- sessed by the linearity of 9 levels concentration which be found 10.0 â?? 5,000.0 ng/mL, r = 0.9996 respectively. Chloroform was used as pretreatment solvent to extract Irbesartan dan Candesartan cilexetil (Internal Standard) from protein binding. The chromatogram of Irbesartan dan Candesartan cilexetil peaks were clearly separated without matrix noises, it was showed by resolution factor > 2. Â